Lesotho : A Safety Net to End Extreme Poverty - World Bank (Washington, DC, 2013)
The objective of this study is to help the government to decide what role safety net and transfer programs should play in the coming 5 to 10 years. It seeks to answer following three questions: (i) can increased spending on transfers accelerate poverty reduction in the medium to long term?; (ii) which groups and aspects of poverty will it make sense to target with transfers?; and (iii) which programs will have the greatest impact at an affordable cost? This study examined such programs in Lesotho both ones that currently exist, and the potential scope for using instruments that may not currently exist. It also widened its scope to examine all programs that transfer public resources directly to households such as agricultural subsidies and university bursaries. It analyzed them through the lens of their impact on the poor because it is important to evaluate public spending and trade-offs in the context of where public funds are currently being spent and what distributional impact they are having. The assumption underlying this analysis throughout the report is that the over-riding objective of both the government and its development partners is to reduce the high levels of poverty and inequality that persist in Lesotho. This report is organized as follows: chapter one explores the country context and fiscal space for public expenditure on social safety nets. Chapter two examines the dynamics of poverty in Lesotho and the characteristics of the major vulnerable groups and discusses which of these groups it will make most sense for the social safety net to target. Chapter three analyzes Lesotho's existing transfer programs. Chapter four reviews institutional and capacity issues. Chapter five presents options for a long-term package of social safety nets and associated costs, makes some recommendations for strengthening existing programs, and suggests which type of programs it might be cost-effective to expand.